A Figura do Coordenador de Projetos no binómio Portugal/Argélia por interligação com as normas HQE - Lopes, Pedro Mezia (2013)
This paper is inserted in the Architecture of the Contemporary Metropolitan Territories PhD programme, and plans to motivate a better understanding of the role of Project Coordinator in Portugal and Algeria, which in Algeria is necessarily intertwined with the HQE - High Quality Environmental - Standards. A detailed description of legislation in Portugal / Algeria governing the Projects Coordinator figure will be consummated, as well as a brief depiction of how the launch of public tenders for projects is structured in Portugal and Algeria. The public projects tendering structure, and the existence of the Suivi phase in Algeria compared with the Technical Assistance in Portugal, has a direct influence in how the projects and construction process take place, and how the principles of HQE standards are put into practice. Subsequently, this article will be part of the author’s PhD Thesis, that intends to take stock of the decade-long intervention in Algerian territory, and at the same time tries to design the future viability of Architectural Portuguese intervention in the Algerian territory.